Observation of Three‐Dimensional Magnetic Reconnection in the Terrestrial Magnetotail. Issue 9 (27th September 2017) - Zhou, Meng; Ashour‐Abdalla, Maha; Deng, Xiaohua; Pang, Ye; Fu, Huishan; Walker, Raymond; Lapenta, Giovanni; Huang, Shiyong; Xu, Xiaojun; Tang, Rongxin
Abstract: Study of magnetic reconnection has been focused on two‐dimensional geometry in the past decades, whereas three‐dimensional structures and dynamics of reconnection X line are poorly understood. In this paper, we report Cluster multispacecraft observations of a three‐dimensional magnetic reconnection X line with a weak guide field (~25% of the upstream magnetic field) in the Earth's magnetotail. We find that the X line not only retreated tailward but also expanded across the tail following the electron flow direction with a maximum average speed of (0.04–0.15) V A, up, where V A, up is the upstream Alfvén speed, or (0.14–0.57) V de, where V de is the electron flow speed in the out‐of‐plane direction. An ion diffusion region was observed by two spacecraft that were separated about 10 ion inertial lengths along the out‐of‐plane direction; however, these two spacecraft observed distinct magnetic structures associated with reconnection: one spacecraft observed dipolarization fronts, while the other one observed flux ropes. This indicates that reconnection proceeds in drastically different ways in different segments along the X line only a few ion inertial lengths apart. Plain Language Summary: Two‐dimensional reconnection model has been employed for decades to interpret the observations in space. However, reconnection sometimes happens in a three‐dimensional manner that is dramatically different from the 2‐D model. The 3‐D dynamics of reconnection is poorly known. By using observations from multiple points in Earth's magnetosphere, we are able to reveal some important aspects of the three‐dimensional dynamics of magnetic reconnection X line, which is characterized by expansion and large gradient in the out‐of‐plane direction. For the first time, we estimate the X line expansion speed using the in situ data. We found that the X line expanded along the electron out‐of‐plane flow direction with a speed much less than the upstream Alfvén speed and a small fraction of the electron flow speed in the out‐of‐plane direction. An ion diffusion region was observed by two spacecraft that were separated about one Earth radius along the out‐of‐plane direction; however, these two spacecraft observed distinct magnetic structures associated with reconnection. This indicates that the characteristic length of X line is on the order of the ion scale. Reconnection produces 3‐D structures on the ion scale in Earth's magnetosphere. Key Points: Cluster multispacecraft observations of a three‐dimensional magnetic reconnection X line with a weak guide field in the magnetotail The X line expanded in the out‐of‐plane direction with a maximum speed less than both the upstream Alfven speed and electron flow speed Reconnection proceeds in drastically different ways in different segments along the X line only a few ion inertial lengths apart